Corporate Social Responsibility, Good Corporate Governance, and Management Compensation against Tax Avoidance - Yeyet Rohyati; Suripto Suripto (Budapest International Research and Critics University, 2021)
This study aims to obtain empirical evidence regarding the influence of Corporate Social Responsibility, Good Corporate Governance, and Management Compensation on Tax Avoidance. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2016-2018. Determination of the sample using purposive sampling technique, obtained a sample of 8 companies with 40 observational data. The analysis technique and hypothesis testing are carried out by using panel data regression analysis through Eviews-9. The results show that Corporate Social Responsibility has a positive effect on Tax Avoidance, Good Corporate Governance has no effect on Tax Avoidance, and Management Compensation has a negative effect on Tax Avoidance.